Molecular Mechanisms of Action of Histidine-rich Glycoprotein in Angiogenesis Inhibition - Lee, Chunsik (Uppsala universitet, Institutionen för genetik och patologi, 2006)
Angiogenesis, de novo synthesis of blood vessels from the pre-existing vasculature, is required both during embryonic development and in pathophysiological conditions. In particular, tumor growth needs new capillary vessels in order to both deliver oxygen and nutrients and to remove toxin and metabolites. Growth of most solid tumors would be restricted to a microscopic size in the absence of neovascularization. Angiogenesis ensues as a result of a shift in the balance between pro- and anti-angiogenic molecules. Histidine-rich glycoprotein (HRGP) is a heparin-binding plasma protein. We showed that HRGP inhibits endothelial cell migration and adhesion to vitronectin. As a consequence, HRGP attenuates growth and vascularization of mouse model tumors. The anti-angiogenic effect of HRGP is mediated by the central histidine/proline (His/Pro)-rich domain, which must be released from the parent molecule to exert its effect. A 35-amino acid residue peptide denoted HRGP330, derived from the His/Pro-rich domain, was identified as a minimal active anti-angiogenic domain of HRGP. HRGP330 induces disruption of molecular interactions required for cell motility, such as the integrin-linked kinase/paxillin complex. Moreover, HRGP330 inhibits VEGF-induced tyrosine phosphorylation of α-actinin, a focal adhesion kinase (FAK) substrate. Consequently, the motility of endothelial cells is arrested. By use of a signal transduction antibody array, we identified FAK, paxillin and growth factor receptor-bound 2 (Grb2) as tyrosine phosphorylated in HRGP330-treated cells. We confirmed that HRGP targets focal adhesions in endothelial cells, thereby disrupting the cytoskeletal organization and the ability of endothelial cells to assemble into vessel structures. A critical role of FAK in HRGP-inhibition of angiogenesis was validated using a FAK inhibitor, geldanamycin, which allowed rescue of endothelial cell actin rearrangement. We identified another potential mechanism in the HRGP/HRGP330 anti-angiogenic effects, exerted through regulation of tumor-associated macrophages (TAMs). HRGP/HRGP330 treatment led to reduced TAM infiltration, which in turn caused a marked decrease in VEGF and MMP-9 levels in the tumor. Taken together, our present studies show that HRGP/HRGP330 target endothelial cell adhesion, migration, focal adhesions, and furthermore, that HRGP is involved in regulation of macrophage infiltration.